A high susceptibility to redox imbalance of the transmissible stages of Plasmodium falciparum revealed with a luciferase‐based mature gametocyte assay. Issue 2 (21st February 2017) - Siciliano, Giulia; Santha Kumar, T.R.; Bona, Roberta; Camarda, Grazia; Calabretta, Maria Maddalena; Cevenini, Luca; Davioud‐Charvet, Elisabeth; Becker, Katja; Cara, Andrea; Fidock, David A.; Alano, Pietro
Summary: The goal to prevent Plasmodium falciparum transmission from humans to mosquitoes requires the identification of targetable metabolic processes in the mature (stage V) gametocytes, the sexual stages circulating in the bloodstream. This task is complicated by the apparently low metabolism of these cells, which renders them refractory to most antimalarial inhibitors and constrains the development of specific and sensitive cell‐based assays. Here, we identify and functionally characterize the regulatory regions of the P. falciparum gene PF3D7_1234700, encoding a CPW‐WPC protein and named here Upregulated in Late Gametocytes ( ULG8 ), which we have leveraged to express reporter genes in mature male and female gametocytes. Using transgenic parasites containing a pfULG8 ‐luciferase cassette, we investigated the susceptibility of stage V gametocytes to compounds specifically affecting redox metabolism. Our results reveal a high sensitivity of mature gametocytes to the glutathione reductase inhibitor and redox cycler drug methylene blue (MB). Using isobologram analysis, we find that a concomitant inhibition of the parasite enzyme glucose‐6‐phosphate dehydrogenase‐6‐phosphogluconolactonase, a key component of NADPH synthesis, potently synergizes MB activity. These data suggest that redox metabolism and detoxification activity play an unsuspected yet vital role in stage V gametocytes, rendering these cells exquisitely sensitive to decreases in NADPH concentration. Abstract : The poorly understood physiology of the mature gametocytes of Plasmodium falciparum was investigated with bioluminescent parasites, revealing that these stages, known to be refractory to virtually all antimalarial drugs, are exquisitely vulnerable if their ability to contrast oxidative stress is impaired.